The educational work of the Confederation of Free German Trade Unions (FDGB) (Institute of International Trade Union Studies [etc.], 1971)
Series of the Institute of International Trade Union Studies, College of the Confederation of Free German Trade Unions "Fritz Heckert" at Bernau.